Seed Storage and Germination Enhancement Methods for Six Economically Important Indigenous Trees of Ethiopia: A Review: REVIEW PAPER - Seid, Mohammed Adefa (Annals of Arid Zone, 2025)
Conservation and sustainable management of Ethiopia’s economically important indigenous tree species are crucial for preserving biodiversity and restoring ecosystems. However, the viability and germination potential of their seeds are often hindered by dormancy, desiccation sensitivity, and improper storage techniques. These limitations in seed storage and poor germination rates present challenges for the sustainable propagation and conservation of these valuable trees. This review paper synthesizes existing knowledge on seed storage behavior, dormancy mechanisms, and germination enhancement techniques for six selected indigenous tree species in Ethiopia, namely, Cordia africana, Vachellia abyssinica, Olea europaea ssp. africana, Millettia ferruginea, Albizia gummifera, and Hagenia abyssinica. It explores the physiological and ecological factors that influence seed longevity and germination success while evaluating various pre-treatment methods such as scarification, stratification, and chemical applications. This review identifies species-specific treatments that improve germination and seed viability, helping afforestation efforts. For instance, the germination rates of C. africana are enhanced by soaking seeds in hot water (70 to 80°C) for 10 to 15 minutes. V. abyssinica can achieve up to a 98% improvement with concentrated sulfuric acid pre-treatment. The germination of O. europaea ssp. africana is enhanced by soaking seeds in hot water (70-80°C) for 10-15 minutes and then leaving them soaked for 12 to 24 hours. Similarly, M. ferruginea benefits from soaking seeds in hot water (70 to 80°C) for 10 to 15 minutes, followed by a 12 hour soak in water. A. gummifera also improves with hot water soaking for 10 to 15 minutes and a subsequent soak of 12 to 24 hours. Finally, H. abyssinica shows enhanced germination rates with the same hot water soaking method for 10 to 15 minutes, followed by a soak of 12 to 24 hours. Additionally, this manuscript assesses the effectiveness of different seed storage strategies in maintaining viability over time. By consolidating findings from diverse studies, this review paper provides critical insights for conservation practitioners, foresters, and policymakers, offering recommendations to improve seed handling practices for afforestation, reforestation, and ecological restoration initiatives. It underscores the need for species-specific approaches to enhance seedviability and propagation success, ultimately contributing to afforestation and biodiversity conservation efforts in the country.